Case report: Adrenal myelolipoma resected by laparoscopic surgery - Feng, Qingbo; Li, Hancong; Chen, Xinyang; Feng, Xuping; Li, Jiaxin (Frontiers in Oncology, 2022)
Introduction: Adrenal myelolipomas are benign tumors composed mainly of lipomatous elements with myeloid cells. With the development of medical imaging technology, the detection rate has gradually increased. We report a case of adrenal myelolipoma successfully excised through the laparoscope and reviewed existing literature in recent ten years to summarize the feasibility of the laparoscopic approach for this tumor. Case Presentation: Herein, we described a case of adrenal myelolipoma resected by laparoscope in a 63-year-old male patient. He did not have any other symptoms except the incidental finding of a left adrenal mass. An abdominal CT examination revealed a mixed-density lesion containing some amount of adipose tissue. In conjunction with the patient’s willingness, we performed a laparoscopic operation to remove the lump. The definite diagnosis was confirmed as an adrenal myelolipoma according to the pathology. The patient recovered well postoperatively and without signs of recurrence at a 5-month follow-up. Conclusion: Adrenal myelolipoma is commonly benign, asymptomatic, and hormonal inactivity. A surgical strategy is suggested for high complication risk patients. The laparoscopic approach is safe and feasible with an obvious advantage over open procedures.